Kuantitas dan Kualitas Nutrisi Pakan Orangutan di Pusat Reintroduksi Orangutan, Wanariset Samboja-Kalimantan Timur - nFN Zuraida (Buletin Plasma Nutfah, 2006)
Orangutan (Pongo pygmaeus) was an endangered species with a decreasing population gradually. To overcome the problem, reintroduction was a good conservation program. This was done through a rehabilitation that aim was ad at increasing the adaptability of orangutan which were adapted to human environment, so that they can survive in their natural habitat. The nutrient adequacy for orangutans while staying in the reintroduction center was very important before they were released into natural habitat. Therefore, the objectives of this study were to find out the kinds of daily feed consumption, nutrient contents and nutrient intake of orangutans at Wanariset Samboja by measuring the average daily nutrient intake of individual orangutans. Data were obtained from eight samples of orangutans in individual cages containing a male and a female at the age of two year old, and three males and three females at the age of four year old. The data of feed consumption were recorded three times daily, namely, morning, noon, evening in terms of feed amount and types, then converted into the nutrient values based on table of nutrient contents listed in standardized table. The differences in nutrient intake based on sex and age were obtained by Duncan analysis. The results of the study showed that the daily nutrient intake of 8 orangutans during 24 hours more than energy expenditure in the cage. Total energy used for 24 hours by female and male orangutans at the age of two years old were 692.57 and 739.60 calories, respectively, whereas the energy used by orangutans at the age of four years old were 1088.84 and 945.57 calories, respectively. Calories consumed from feed at the age of two years for female and male were 1042,10 and 1066,60 calories respectively while at the age of four years for female and male were 1402,03 calories and 1227,40 calories respectively. According to the above data energy consumed from feed was more than energy expenditure. It was concluded that feeding consumption given at Wanariset samboja was adequate. AbstrakOrangutan (Pongo pygmaeus) adalah salah satu jenis satwa langka yang populasinya semakin menurun. Untuk mengatasi masalah ini dilakukan upaya pengembalian orangutan ke habitat aslinya dengan sistem rehabilitasi. Dalam hal ini ketersediaan pakan merupakan hal yang penting. Penelitian ini bertujuan untuk mengetahui informasi penyediaan pakan, kandungan, dan asupan nutrisi harian orangutan di Wanariset Samboja. Data yang diambil berasal dari delapan sampel orangutan di kandang individu yang terdiri atas satu ekor jantan dan satu ekor betina umur 2 tahun, serta tiga ekor jantan dan tiga ekor betina umur 4 tahun. Jumlah dan jenis pakan yang dikonsumsi dikonversi ke nilai kandungan nutrisi yang terdapat dalam tabel kandungan bahan makanan. Perbedaan asupan nutrisi berdasarkan jenis kelamin dan umur diketahui dengan uji Duncan. Hasil penelitian menunjukkan bahwa asupan kalori harian delapan orangutan contoh selama 24 jam lebih banyak dibandingkan dengan kalori yang dikeluarkan orangutan selama di kandang. Total energi yang dikeluarkan selama 24 jam oleh orangutan betina dan jantan berumur 2 tahun berturutturut adalah 692,57 dan 739,60 kalori, sedangkan untuk umur 4 tahun adalah 1088,84 dan 945,61 kalori. Kalori yang didapat dari makanan untuk orangutan betina dan jantan umur 2 tahun berturut-turut adalah 1042,10 dan 1066,60 kalori dan untuk orangutan yang berumur 4 tahun berturut-turut adalah 1402,03 dan 1227,40 kalori. Dengan demikian, jumlah energi yang didapat dari makanan lebih besar dibandingkan dengan energi yang dikeluarkan. Berdasarkan data tersebut dapat disimpulkan jumlah pakan yang diberikan di pusat rehabilitasi orangutan mencukupi kebutuhan.